Identifying the cognitive and metacognitive approaches using post editing techniques toward English-Indonesian and Indonesian-English Text - Amaliah (GoAcademica Research & Publishing, 2023)
The aims to identify toward English-Indonesian and Indonesian-English Text by using cognitive approach and to identify toward English-Indonesian and Indonesian-English Text by using metacognitive approach. Related to cognitive approaches and metacognitive approaches; The person engages in a lot of metacognitive processes. The respondent modified the submit-text using their own methods for the total results. In order to construct a comparative target text, the respondent first retranslated using Google Translator to create the target texts. Second, compared the two translated versions of the text that Google Document (GD) and Google Translate created (GT). The participant appears to be able to rely on her logical reasoning and solely has faith in the resources that have been made available to her.TAP translation techniques work to help students develop a positive attitude about translation as an activity that incorporates a great deal of cognitive and metacognitive activities. The research utilized a qualitative approach with a case study method where the participants is asked to conduct a post editing activity utilizing the Think Aloud Protocol or TAP strategy. The strategies use for collecting the data are: (1) examining, (2) analyzing, (3) categorizing and (4) assessing. Coding analysis is used to analyze the data. Therefore, the goal of the post-editing is basically to identify a gap or a problem in the MT output and find a solution to the problem to achieve the acceptable final output.